THE EFFECT OF COPPER COMPOSITION 1, 3 AND 5 WT% Cu MIXED IN CONVENTIONAL AND MECHANICAL ALLOYING ON MICROSTRUCTURE AND HARDNESS OF Ti-Cu ALLOY USING HOT PRESSING-SINTERING METHODS - Fitri, Anisa
Ti-Cu alloy as bone implant material has many advantages such as biocompatibility and good corrosion resistance, low elastic modulus, anti-bacterial properties and has good strength and hardness. One of the implant-making methods is powder metallurgy. However, products from powder metallurgy still have a relatively high % pore area. The presence of these pores can reduce mechanical strength and become a stress concentrator. Ti-Cu mixing by mechanical alloying (MA) is an effort to reduce pore because this process will produce a homogeneous and fine powder. In addition, there is also hot pressing-sintering method (HP-S) which function is to deform the powder at high temperaturs so it will produce a good mechanical interlocking and more compact green body. A series of experiments have been carried out to obtain the influence of the composition of copper (1, 3 and 5 wt%) and the powder mixing mechanism on the microstructure and hardness of Ti-Cu alloys. Ti-Cu powder with an average size of 44 µm was mixed conventionally and mechanical alloying for 1 hour. After that, the hot press process was carried out at a temperatur of 500 °C with a pressure of 100 Bar and continued with a sintered process at a temperatur of 950 °C which was held for 2 hours. Then the sample was prepared for microstructural observations using optical microscopy and SEM and hardness testing using the Vicker Hardness Test with a load of 300 grams. The microstructure observation showed that in Ti alloys (1, 3 and 5 wt% Cu) the results of hot pressing-sintering appeared ?-Ti and Ti2Cu phases which form a lamellar structure. The Ti2Cu phase that appears also increases within the increasing of Cu. While in the hot press stage, the elements Ti and Cu are still in the free element. In general, the increasing copper content of the % pore area and the size of the grain will be smaller while the hardness will increase. In addition, the integration of Ti-Cu through mechanical alloying, followed by the hot pressingsintering method will deliver a smaller% of the pore area and higher hardness than conventional mixing. The smallest %pore area, the largest grain size, and the highest hardness value are found in the Ti-5wt% Cu alloy from hot pressingsintering combined through mechanical alloying. The smallesb %pore area, the largest grain size, and the highest hardness value are 1.55%; 28,378 µm and 456.7 HV.